2007
DOI: 10.1158/1078-0432.ccr-06-2889
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Sorafenib in Combination with Gefitinib in Patients with Refractory or Recurrent Non–Small Cell Lung Cancer

Abstract: Purpose: To evaluate the combination of sorafenib and gefitinib in patients with advanced nonŝ mall cell lung cancer. Experimental Design: In this dose-escalation trial, patients received oral sorafenib (200-400 mg) twice daily with gefitinib (250 mg orally) once daily to identify the recommended dose for phase II trials (RDP; part A). The pharmacokinetics of the RDP were characterized further in additional patients (part B) receiving single-agent gefitinib or sorafenib for 21days followed by a 7-day washout w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 40 publications
6
49
0
1
Order By: Relevance
“…The median PFS interval in our study was 2.8 months, similar to previously reported data [37]. However, some studies of less heavily pretreated or treatment-naïve patients with NSCLC reported better outcomes, with median PFS times of 4 -5 months [32,38]. In advanced/metastatic NSCLC, the median OS time on first-line therapy rarely exceeds 11 months and the median PFS duration is usually around 5 months [39 -42].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The median PFS interval in our study was 2.8 months, similar to previously reported data [37]. However, some studies of less heavily pretreated or treatment-naïve patients with NSCLC reported better outcomes, with median PFS times of 4 -5 months [32,38]. In advanced/metastatic NSCLC, the median OS time on first-line therapy rarely exceeds 11 months and the median PFS duration is usually around 5 months [39 -42].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, data obtained from our phase I clinic on 683 participants having various tumor types showed that patients treated with low dose levels did not fare worse [31]. Previously reported RRs in heavily pretreated NSCLC patients treated in disease-specific phase I clinical trials were in the range of 3%-15% [32][33][34]. Most of our patients with NSCLC (77 of 85, 90.5%) were enrolled in studies that administered targeted agents.…”
Section: Discussionmentioning
confidence: 83%
“…This occurred at doses lower than the single-agent doses. There is also phase I evidence that sorafenib (400 mg bid) can be safely combined with the EGRF inhibitors erlotinib (150 mg) and gefitinib (250 mg) with promising antitumor activity [Adjei et al 2007;Duran et al 2007]. Four phase II trials are evaluating the efficacy of sorafenib with erlotinib in patients with advanced NSCLC in the first-line setting.…”
Section: Vegf Receptor Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…combination (53) Sorafenib + gefitinib Evaluated this combination in Sorafenib combined with gefitinib was well tolerated, with advanced NSCLC (54) promising efficacy in patients with advanced NSCLC.…”
Section: Combination Study Findingsmentioning
confidence: 99%